Commensurability of Science During Paradigm Shifts And Standards Of Progress: Edited by Doğa Özden - Malik, Hassan (The Oracle, 2021)
In this essay, I will talk about the development of scientific theories in the philosophy of science. I will explain the way in which science is thought to be created by Thomas Kuhn in “The Structure of Scientific Revolutions”. As a result of the Kuhn’s description of science as a framework consisting of paradigms, Kuhn contends that scientific advancement is noncumulative. For Kuhn, an old paradigm must be supplanted irrationally in entire by a new and incommensurable alternative paradigm through the process of a scientific revolution (Kuhn, 12). However, I will argue that Kuhn’s position on this matter is entirely not correct. Instead, I argue that, within the paradigmatic structure of science that Kuhn advances, progress within the paradigms of science can be shown to be cumulative and rational. Examples of this can be found in the various ways in which scientists continually reference and operate with the work of the old paradigm despite their adherence to the new. After my argument, a reaction from Kuhn is imagined on the alleged correspondence between paradigms. I show that Kuhn would find that although paradigms may communicate among one another the standards by which they communicate and ultimately compare among one another is inherently irrational and cannot be justified. At last, I attempt to explain away Kuhn’s imagined reaction by arguing that rational discussion and judgement among paradigms is possible using experience in our epistemological pursuits.